9=3(k-1)+k

Simple and best practice solution for 9=3(k-1)+k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=3(k-1)+k equation:


Simplifying
9 = 3(k + -1) + k

Reorder the terms:
9 = 3(-1 + k) + k
9 = (-1 * 3 + k * 3) + k
9 = (-3 + 3k) + k

Combine like terms: 3k + k = 4k
9 = -3 + 4k

Solving
9 = -3 + 4k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-4k' to each side of the equation.
9 + -4k = -3 + 4k + -4k

Combine like terms: 4k + -4k = 0
9 + -4k = -3 + 0
9 + -4k = -3

Add '-9' to each side of the equation.
9 + -9 + -4k = -3 + -9

Combine like terms: 9 + -9 = 0
0 + -4k = -3 + -9
-4k = -3 + -9

Combine like terms: -3 + -9 = -12
-4k = -12

Divide each side by '-4'.
k = 3

Simplifying
k = 3

See similar equations:

| y=cos(2y) | | 2l=21 | | 7x-112=0 | | 21=6n | | 5X+(3X-20)=500 | | b-2b=15 | | 3x-105=0 | | f(y)=cos(2y) | | -3x+6(5x-2)=-6 | | hot+girl= | | 8(x-2)=5x+11+3x | | 3x+3(x+15)=15 | | 4n=0.56 | | x^2y-9y+3x-27=0 | | 5(x+-4)+2x=14 | | y=4(1.666666667)+6 | | 5x-15=20-2x | | 10cos(x)+sin^2(x)=0 | | mx+nc=y | | 2x^4-8=0 | | 2x^5-8=0 | | (-25)x(-13)= | | -25x-13= | | 8.3(x-31)=-37.35 | | 2z^2+7z+5=6z^2 | | (logx)6561=8 | | 9x+18=5x+38 | | x+4(-1)=8 | | 7x-4(-2x+7)=-193 | | X+7=3(x+7)-19 | | R=176-0.8x | | -4+(-2)x-3= |

Equations solver categories